Excellent Stability of Perovskite Solar Cells by Passivation Engineering (Solar RRL 8∕2018). Issue 8 (6th August 2018) - Gao, Lili; Huang, Sheng; Chen, Lin; Li, Xiaolei; Ding, Bin; Huang, Shiyu; Yang, Guanjun
Abstract : A novel and convenient strategy to improve the stability of perovskite solar cells by introducing thiourea into perovskite is developed by Guanjun Yang and co‐workers (article no.1800088 ). Thiourea passivates perovskite by forming Pb–S bonds on the outermost layer of perovskite and lath‐shaped grain among perovskites, and thereby improves the oxygen, light and thermal stability and reduces hysteresis. In addition, the thiourea additive significantly improves the quality of perovskite crystal for the adduct of PbI2 with thiourea as the Lewis base. Devices with thiourea additive achieve high efficiencies of 19.57% and unencapsulated devices retain 98% of original efficiency after two months under air conditions, showing excellent stability.